Modeling and multi-objective optimal sizing of standalone photovoltaic system based on evolutionary algorithms - Ridha, Hussein Mohammed (2020)
The standalone photovoltaic (SAPV) system is one of the most widely used applications of the PV system. However, the main drawbacks of this system are the high capital investment and low energy efficiency mainly due to the simple PV model and the ineffective sizing method of SAPV system. Therefore, precisely modeling method to determine the unknown parameters of the PV module is essential to give a realistic evaluation for the extracted energy of the PV array. Moreover, optimization of the standalone PV system is necessary to maximum the reliability and minimize the total cost of the system in both urban and rural areas.